Effect of Psychological Factors and Workload on Midwife Performance in the Integreted Antenatal Care in Pati, Central Java - Marfuah, Siti; Tamtomo, Didik; Suryono, Arief (Journal of Maternal and Child Health, 2016)
Background: One of the sensitive population health indicators is maternal mortality rate (MMR). One of the MMR determinants is antenatal care (ANC) coverage. This study aimed to determine the effect of psychological factors and workload on midwife work performance in the integrated antenatal care in Pati, Central Java.Subjects and Method: This was analytic observational study with cross sectional design. This study was conducted in Pati, Central Java. A total of 130 midwives was selected for this study by stratified random sampling. The dependent variable was work performance. The independent variable motivation, self eficacy, self actualization, workload, and midwife peer group as the contextual variable. The data were collected by a set of questionnaire. The data were analyze by linear multilevel multiple regression model.Results: Motivation (b=0.15; 95% CI =0.01 to 0.29; p=0.035), self actualization (b=0.21; 95% CI=- 0.01 to 0.40; p=0.031), and self efficacy (b=0.15; 95% CI =-0.01 to 0.31; p=0.048) had positive and statistically significant effects on work performance. Workload (b=-0.26; 95% CI=-0.53 to 0.01;p=0.056) had negative and nearly significant effect on work performance. There was a contextual effect of midwife group on work performance. ICC=17.51%; likelihood ratio=- 262.55; p=0.006.Conclusion: Motivation, self actualization, and self efficacy have positive effects on work performance. Workload has negative effect on work performance. Midwife group has a contextual effect on work performance.Keywords: psychological factors, workload, work performance, midwife.Correspondence: Siti Marfuah. Academy of Midwifery Bakti Utama, Pati, Central Java. Email: sty_marfuah@yahoo.com. Mobile: 085729885380Journal of Maternal and Child Health (2016), 1(3): 138-145https://doi.org/10.26911/thejmch.2016.01.03.01